Understanding gender differences in Korean emotional expressions for increased cultural competency of social workers. (November 2016) - Sohn, Sunju; Park, Mi-Sook
This study identified Korean emotional expressions described by male and female Koreans, who disagreed about their use under similar circumstances. The authors assessed the meanings of 504 'emotional' terms, rank-ordered them according to how high the participants rated various emotions and used the kappa statistic to discern gender-based incongruence. The findings showed that identical emotional expressions might have nuanced differences in mutually exclusive emotional states. This was particularly apparent among males, who reported using the same expressions in two different situations. The results strengthen social workers' language-centred activities, which help them assist Koreans and Korean-Americans to use helping processes.